PENGARUH SELF EFFICASY DAN REWARD TERHADAP KINERJA KARYAWAN NUSANTARA OPTIK - Ratnasari, Ika; Peni Indarwati; Hamzah Pujiono (Bajang Institute, 2024)
This research aims to examine the influence of self-efficacy and work rewards on employee performance. This research uses a survey method by distributing questionnaires to respondents who are Nusantara Optik employees, with a total of 34 respondents. Independent variables include self-efficacy and reward, while the dependent variable is employee performance. Data analysis was carried out using regression techniques to assess the extent to which these independent variables can predict employee performance. The results of this research show that the self-efficacy variable has a positive and significant effect on employee performance. Meanwhile, the reward variable also has a positive and significant effect on the performance of Nusantara Optik employees